Mengatasi Tantangan Manajemen Kelas di Era Digital - Ain, Inggit Saraswati Nur; Shudarsono, Muhamad; Febrina, Trismalia; Rohim, Abdul; Aulia, Shindy (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
In the digital age, technology has changed the way teachers teach and students learn, bringing both new opportunities and complex challenges to classroom management. Students now have extensive access to information through the internet, which can either support or distract them from learning. The use of devices such as computers and learning apps requires teachers' ability to integrate these technologies effectively. Many interactions between teachers and students are now online, demanding adaptations in the way we communicate and build relationships. Managing a virtual classroom requires a different approach to monitoring student attendance, participation and engagement. Digital devices can be a distraction, so it is important to keep students focused during learning. Teachers need to teach and enforce digital etiquette, including good online behavior and cybersecurity. Not all students have equal access to devices and the internet, creating gaps in learning. Therefore, teachers and students need to have adequate digital literacy to utilize technology effectively. Addressing these challenges requires a comprehensive strategy, including teacher training, adaptive curriculum development and policies that support the use of technology in education. Thus, technology can be a powerful tool to improve the quality of education and prepare students for a digital future.